Status Sosial Unsur Penokohan Pada Cerita Pendek â€œSang Guru Jukiâ€ Karya Ahmad Tohari - Ardhian Nurhadi; Nova Daniar Adriyanti (Indonesian Language Education and Literature, 2020)
This study aims to examine and determine the function of social status and role of the behaviour and character of figures in the community system. The data source in this study is a short story entitled "Sang Guru Juki" by Ahmad Tohari. The resulting data is in the form of quotes that contain aspects of social values and status in the short stories. Researchers' data collection techniques used the observation and note technique. The results of the short story analysis contain vital social elements and values, especially in the characterization elements. Some of the intrinsic aspects conveyed in the story have a strong comparison in giving the message through the characters, especially the Juki character. The social element developed in the report include moral aspects, ethical aspects, and educational aspects. The Juki character depicted in the story has a profession as a teacher. However, the behaviours and attitudes that are built into the story do not show Juki's character as a teacher who must be emulated by his students. Juki tends to take advantage of their social status and role to fulfil their desires and desires.Penelitian ini bertujuan untuk menelaah dan mengetahui fungsi status sosial dan peran dalam hubungannya dengan perilaku dan watak tokoh dalam sistem masyarakat. Sumber data pada penelitian ini adalah cerpen berjudul Sang Guru Juki karya Ahmad Tohari. Data yang dihasilkan berupa kutipan-kutipan yang memuat aspek-aspek nilai sosial dan status dalam cerpen. Teknik pengumpulan data peneliti menggunakan teknik simak dan catat. Hasil analisis cerpen memuat unsur dan nilai sosial yang kental terutama pada unsur penokohannya. Beberapa unsur intrinsik yang disampaikan dalam cerita memiliki komparasi kuat dalam penyampaian amanat melalui tokoh-tokohnya terutama tokoh Juki. Aspek sosial yang dikembangkan dalam cerita meliputi aspek moral, aspek etika, dan aspek pendidikan. Tokoh Juki digambarkan dalam cerita memiliki profesi sebagai seorang guru. Namun perilaku dan sikap yang dibangun dalam cerita tidak menunjukkan watak Juki sebagai seorang guru yang harus diteladani oleh muridnya. Juki cenderung memanfaatkan status dan peran sosialnya untuk memenuhi nafsu dan keinginannya sendiri.